Perencanaan Rute Optimal Kunjungan Destinasi Wisata Bandung dengan Algoritma Dijkstra Pada C++ - Khoir, Farhan Ramadhan; Subandri, Anatasia Aulienda; Alanshori, Fatih Nurrobi; Solihah, Zulfa Maylafaiza Hadiatus; Munawir, Munawir; Perdana, Abdi Surya (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Bandung, as one of the attractive and popular tourist destinations in Indonesia with a variety of destination choices. The development of the tourism sector in Bandung does not only focus on attracting tourists, but also includes improving infrastructure and accommodation facilities. With more than 825 tourist destinations in Bandung, visiting tourists realize how important it is to choose the best route to maximize their travel experience. This research focuses exclusively on discussing the application of the Dijkstra Algorithm with the C++ programming language to increase travel efficiency to tourist destinations in Bandung. Dijkstra's algorithm is a very effective method in determining the shortest route and is widely used. Performance comparison between Dijkstra's Algorithm and other algorithms shows the significant superiority of Dijkstra's Algorithm. This advantage can be attributed to the use of non-negative weights and the simple and easy to understand nature of the graph, making this research relevant and has the potential to make a positive contribution in improving the tourist experience in Bandung.